Comparison between conventional tomography & radiovisiography methods for assessment of presurgical dental implants - Talaei Pour AR; Mehralizadeh S.; Mesgarzadeh A (Tehran University of Medical Sciences, 2005)
Statement of Problem: Musculoskeletal disorders (MSDs) are major parts of the occupational diseases in workplaces. Protection from such diseases is dependent on assessment and improvement of job postures by using job analysis methods in ergonomics. Purpose: This study was aimed to evaluate ergonomic conditions in dental professions by rapid entire body assessment (REBA) in Birjand city and also to assess the relation between MSDS in different parts of the body and work conditions. Materials and Methods: This study was a descriptive-analytical approach performed on 48 persons working at different professions by using REBA method. The prevalence of MSDs was obtained by using Nordic Musculoskeletal Questionnaire (NMQ). The data were analyzed by independent t-test, Chi-square and Fisher tests with P<0.05 as the limit of significance. Results: In this investigation, the prevalence of disorders for different parts of the body was as follows: 65% for neck, 60% for back, 38% for shoulders, and 31% for wrist. These disorders were higher in women than men except for the back. There were significant correlation between disorders of femur and foreleg with work history, ankle and sole with body mass index (BMI), and MSDs with work conditions (P<0.05). Conclusion: It is concluded that the work conditions and postures need to be improved. In addition the level of dental professional education regarding biomechanical hazardous effects as well as correct work conditions and postures should be increased.